An evaluation of teaching practice: Practicum - Aijaz Ahmed Gujjar; Muhammad Ramzan; Muhammad Jamil Bajwa (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2011)
Teaching practice is an important place in teacher training, it is the theoretical part of teacher training. The purpose of this study was to evaluate the teaching practice, for the purpose a 22 item questionnaire was developed and pilot tested, the internal consistency (Cronbach Alpha) value of the questionnaire was 0.73.Five research questions were made for the study. 650 student teachers throughout the country from 26 teacher training institutions were considered the sample of the study, by selecting 25 student teachers randomly from each institution. The data collected through questionnaire was coded and analyzed through SPSS XII and Stat Pac calculator in terms of frequency, percentage and chi square. The study finds that majority of the student teachers is not given demonstration lessons in all the subjects, duration of teaching practice is not appropriate to develop teaching skills, the method of evaluation in practical component is not appropriate, choice of the student teachers is not considered while assigning the lesson, proportion of theory and practice not appropriate. It is recommended that that the student teachers should be given demonstration lessons before practice teaching, the duration of the teaching practice may be increased, theory and practice should be made proportionate, the student teachers should be made responsible for what they do, this can only be achieved if their choice in the selection of lesson is also considered..
Keywords: 330; Teaching Practice; Lesson; Duration; Theory